Seeking Racial and Ethnic Parity in Preschool Outcomes: An Exploratory Study of Public Montessori Schools vs. Business-as-Usual Schools - Lillard, Angeline S.; Tong, Xin; Bray, Paige M. (Journal of Montessori Research, 2023)
Montessori pedagogy is a century-old, whole-school system increasingly used in the public sector. In the United States, public Montessori schools are typically Title I schools that mostly serve children of color. The present secondary, exploratory data analysis examined outcomes of 134 children who entered a lottery for admission to public Montessori schools in the northeastern United States at age 3; half were admitted and enrolled and the rest enrolled at other preschool programs. About half of the children were identified as White, and half were identified as African American, Hispanic, or multiracial. Children were tested in the fall when they enrolled and again in the subsequent three springs (i.e., through the kindergarten year) on a range of measures addressing academic outcomes, executive function, and social cognition. Although the Black, Hispanic, and multiracial group tended to score lower in the beginning of preschool in both conditions, by the end of preschool, the scores of Black, Hispanic, and multiracial students enrolled in Montessori schools were not different from the White children; by contrast, such students in the business-as-usual schools continued to perform less well than White children in academic achievement and social cognition. The study has important limitations that lead us to view these findings as exploratory, but taken together with other findings, the results suggest that Montessori education may create an environment that is more conducive to racial and ethnic parity than other school environments.